PERAN DAN STRATEGI PUBLIC RELATIONS DALAM PENGEMBANGAN ORGANISASI NIRLABA - Widiantara I Komang Agus (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
The  development  of the world  of  public  relations  (PR) is  growing  very  rapidly.  This progress is a positive result for institutions / institutions / companies. Even in the current digital era, the role of public relations is very strategic and effective in building image, credibility and influence in the eyes of the public, especially for  nonprofit organizations. PR has  a role as expert  advisor  (Expert  Presciber) in  finding  solutions  to  problems  with  public  relations. Communication Facilitator (Communication Facilitator) positions PR as a communicator or mediator to bring management / leadership in terms of hearing what is desired and expected by the public. Facilitator The Problem Solving Process The facilitator is an important task that can be used by Communication Technicians who are directly involved in the practice of public relations as journalists to gather positive news from nonprofit organizations. Sales organizations, nonprofit organizations, PR strategies must be maximized. Keywords: Public Relations (PR), Nonprofit Organization, Strategy